Functional Turmeric–Tamarind Jelly Drink with Grass Jelly Extract as an Alternative for Dysmenorrhea Relief - Safira , Diandra; Srimiati, Mia (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2026)
Dysmenorrhea is experienced by a large proportion of adolescents and women of reproductive age, affecting quality of life and daily activities. Turmeric–tamarind herbal drinks have long been used as a non-pharmacological approach for managing menstrual pain; however, conventional liquid preparations often have limited product variation and suboptimal sensory appeal. A jelly-based format may enhance sensory acceptability while maintaining functional benefits. This study aimed to analyze the effect of grass jelly leaf extract addition on the sensory characteristics, proximate composition, antioxidant activity, and curcumin content of turmeric–tamarind jelly drinks. This experimental study employed a completely randomized design with several concentrations of grass jelly leaf extract (0%, 50%, 65%, 80%, 95%). Organoleptic data (hedonic and hedonic quality) were tested for normality using the Kolmogorov–Smirnov test, followed by Kruskal–Wallis and Mann–Whitney tests for significant parameters. Chemical analyses, including proximate composition, dietary fiber, antioxidant activity (% inhibition via DPPH spectrophotometry), and curcumin content (HPLC-PDA), were presented descriptively. The hedonic quality test indicated that grass jelly extract significantly affected color, aroma, taste, and texture attributes (p<0.05), although it did not alter panelists’ preference levels. The selected formulation (65%) exhibited a high total dietary fiber content (5.87%), with notably higher insoluble fiber (0.44%) compared to the control (0.08%). Its antioxidant activity (12.02% inhibition) was slightly higher than that of the control (11.15% inhibition), while curcumin levels (108.53 mg/kg) remained preserved despite a reduction from the control formulation (233.61 mg/kg). Overall, the turmeric–tamarind jelly drink enriched with grass jelly leaf extract demonstrated favorable sensory properties and improved functional value, indicating its potential as a natural beverage to support dysmenorrhea management.